Efeito residual de herbicidas em soja, amendoim e crotalária e sua toxicidade em organismos não-alvo - Schedenffeldt, Bruna Ferrari (Universidade Federal de São Carlos, 2023)
The use of herbicides, especially those with long persistence, can impact the productivity of agricultural crops and terrestrial and aquatic ecosystems. The objective of this study was to evaluate the residual effect of different doses of the herbicides indaziflam, sulfentrazone, and clomazone on the growth and development of Crotalaria juncea L., Arachis hypogaea L., and Glycine max (L.) Merr. The acute, chronic, and avoidance effects on Eisenia andrei (Bouché) and acute toxicity on the macrophyte Lemna minor were also assessed. The experiment was divided into two parts, with the first part conducted in a greenhouse following a completely randomized design (CRD) for each crop (soybean, sunn hemp, and peanut) and herbicides (indaziflam, sulfentrazone, and clomazone) in a 6 x 5 factorial arrangement, with five replications, the first factor consisted of 6 different doses (0, 1/8D, 1/4D, 1/2D, 1D, and 2D) of herbicides, where "D" represents the commercially recommended dose for sugarcane cultivation. The second factor comprised 5 sowing periods (0, 10, 20, 40, and 60 days after application - DAA) for the crops. Plants were evaluated for phytotoxicity, height, leaf area, and dry aboveground biomass at 56 days after seeding. The acute assay with E. andrei followed a completely randomized design (CRD) encompassing six concentrations (0.0; 10.0; 100.0; 500.0 and 1,000.0 mg a.i. kg-1 soil) for each herbicide, with five replicates. The avoidance test followed a CRD with five sublethal concentrations. For clomazone and indaziflam, concentrations were 1.0; 10.0; 50.0; 75.0 and 100.0 mg a.i. kg-1, while for sulfentrazone, concentrations were 1.0; 10.0; 25.0; 50.0 and 75.0 mg a.i. kg-1, also with five replicates. The chronic assay adopted the same guidelines as the acute assay, with adults kept for 28 days, followed by collection and counting of juveniles and eggs at 56 days. The herbicide doses were clomazone 1.0; 10.0; 25.0; 50.0 and 75.0 mg a.i. kg-1, sulfentrazone 1.0; 10.0; 100.0; 500.0 and 750.0 mg a.i. kg-1, and indaziflam 1.0; 10.0; 50.0; 75.0 and 100.0 mg a.i. kg-1. The assays with L. minor involved exposing the macrophytes for 7 days to analyze the effect of clomazone and sulfentrazone at concentrations of 0.10; 1.07; 3.44; 11.16; 36.40 and 118,0 mg L-1, and for indaziflam at concentrations of 0.03; 0.06; 0.09; 0.12; 0.15 and 0.18 mg L-1, for a period of 7 days. It was observed that C. juncea plants were extremely sensitive to the herbicide indaziflam, regardless of dose or seeding period, showing reductions in all analyzed parameters. In contrast, the phytotoxicity of sulfentrazone and clomazone decreased from 20 DAA at all doses used. A. hypogaea was highly sensitive to the herbicides indaziflam and sulfentrazone, especially at higher doses, regardless of seeding period, with reductions in all analyzed parameters. G. max was also extremely sensitive to indaziflam, with no significant influence of dose or seeding period on all analyzed parameters. The same occurred with the application of sulfentrazone at 0 and 10 DAA at doses of 600.0 and 1,200.0 g a.i. ha-1. In the acute toxicity analysis, the herbicides clomazone and sulfentrazone were moderately toxic (LC50 = 10-1,000 mg kg-1 soil) to earthworms of the species E. andrei, corresponding to an LC50 of 184.12 mg a.i. kg-1 and 1,000 mg a.i. kg-1, respectively. It was not possible to estimate the lethal dose for the herbicide indaziflam. In the avoidance behavior analysis, the herbicide sulfentrazone induced avoidance by E. andrei from the minimum tested concentration, while clomazone and indaziflam induced avoidance at concentrations of 50.0 and 75.0 mg a.i. kg-1 and 75.0 and 100.0 mg a.i. kg-1, respectively. Chronic exposure of earthworms impacted reproduction, with clomazone having an EC50 of 0.572 mg kg-1. Sulfentrazone had an EC50 of 0.3941 mg kg-1. It is noteworthy that all herbicides, including indaziflam, had an EC10 of 1.0 mg kg-1. Finally, the herbicides showed moderate toxicity to the aquatic plant L. minor, resulting in significant reductions in fresh biomass, even at lower concentrations.
Residual effect of herbicides on soybean, peanut, and crotalaria and their toxicity to non-target organisms
Keywords: Ecotoxicologia; Eisenia andrei; Fuga; Lemna minor; Persistência; Carryover; Ecotoxicology; Avoidance; Persistence; CIENCIAS AGRARIAS::AGRONOMIA::FITOSSANIDADE; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA